Psychiatry as a Career Choice Amna Awais1, Neha Nadeem1, Muhammad Kashif Mehmood 1, Ayesha - Amna Awais , Amna Awais; Neha Nadeem, Neha Nadeem; Muhammad Kashif Mehmood, Muhammad Kashif Mehmood; Aysha Younis, Aysha Younis (Students’ Supplement of Journal of Rawalpindi Medical College, 2022)
Background: To determine frequency of students in Rawalpindi Medical University who would opt for psychiatry as their future career. Along with that we will determine the reasons which encourage or discourage students from choosing Psychiatry. Subjects and Methods: A cross-sectional study was conducted at Rawalpindi Medical University, including MBBS students of the five academic years. All study participants were given a semi-structured questionnaire. The data was entered and analyzed using SPSS version 22 and all categorical variables were expressed both as frequencies and percentages. Results: Psychiatry was the third most common career choice (10.2%) following Surgery (31.8%) and Medicine (26%). However, trend of opting for Psychiatry as a career specialty declined with the advancing academic years. Majority of the respondents who were in favor of Psychiatry had a rural background and belonged to a high socio economic group. Females (11.1%) were slightly more inclined towards this specialty compared to their males (7.8%). Among the reasons for choosing Psychiatry as career specialty, the most common ones were ‘’need to help people with mental illness’’ (89.8%), ‘’need for more Psychiatrists in Pakistan’’ (89.1%) and ‘’interest in the subject’’ (89.9%). Most frequently opted reasons for not choosing this field were ‘’don’t suit my temperament (68.4%)’’. ‘’can negatively affect my mental health’’ (43.1%) and ‘’work is not clinical enough’’ (42.7%). Conclusion: Students showed a stronger inclination towards psychiatry as compared to their peers in most countries worldwide. However, the popularity of Psychiatry as a career choice declined as the academic years progressed. This could be attributed to a variety of factors including experiencing clinical rotations in Psychiatry during the undergraduate program and poor understanding of the pathophysiology of psychiatric diseases. Key Words: Student, career choice, psychiatry, specialty